How Law Responds to Technological Development? - Ayon Diniyanto; Heris Suhendar (Universitas Negeri Semarang, 2020)
Law and technological development must go hand in hand. The speed of technological development must be balanced with a fast legal response. Laws that are not quick in responding to technological developments can certainly result in weak regulations and even a legal vacuum in the technology development sector. The technology industry in the fields of financial technology (fintech), online transportation services, and digital health services continues to develop. Without strong regulation, these sectors will have a weak legal basis. The impact faced can be in the form of misappropriation by irresponsible individuals and causing harm to the wider community. Given that sectors such as fintech, online transportation services, and digital health services are related to the interests of the wider community. The state must exist by making laws or regulations that can respond quickly to technological developments. Indonesia as a rule of law must make all aspects run according to the law, including technological developments that produce products. This paper examines the extent to which the speed of law in Indonesia in responding to technological developments.